Numerical solution of Riemann-Hilbert problems: Painleve II - Olver, S (Unspecified, 2009)
We describe a new spectral method for solving matrix-valued Riemann-Hilbert problems numerically. We demonstrate the effectiveness of this approach by computing solutions to the homogeneous Painleve II equation. This can be used to relate initial conditions with asymptotic behaviour.